2019
DOI: 10.3390/md17060353
|View full text |Cite
|
Sign up to set email alerts
|

Kabirimine, a New Cyclic Imine from an Okinawan Dinoflagellate

Abstract: On our quest for new bioactive molecules from marine sources, two cyclic imines (1, 2) were isolated from a dinoflagellate extract, inhibiting the growth of the respiratory syncytial virus (RSV). Compound 1 was identified as a known molecule portimine, while 2 was elucidated to be a new cyclic imine, named kabirimine. The absolute stereochemistry of 1 was determined by crystallographic work and chiral derivatization, whereas the structure of 2 was elucidated by means of spectroscopic analysis and computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…A previous report also indicated that portimine has much lower toxicity than the other cyclic imine toxin [24]. In contrast, several studies reported that portimine exhibits toxicity in several cells in culture [25,26]. Similarly, in our study, portimine was toxic to peripheral blood mononuclear cells even at 1 nM (data not shown).…”
Section: Discussionsupporting
confidence: 73%
“…A previous report also indicated that portimine has much lower toxicity than the other cyclic imine toxin [24]. In contrast, several studies reported that portimine exhibits toxicity in several cells in culture [25,26]. Similarly, in our study, portimine was toxic to peripheral blood mononuclear cells even at 1 nM (data not shown).…”
Section: Discussionsupporting
confidence: 73%
“…Named after their common structural motif (shaded in blue, Figure 1), these toxins can be further classified by the size of the cyclic imine ring, with either 7,6-spirocyclic systems (as in the spirolides, e.g. spirolide A (1), pinnatoxins, and pteriatoxins) or 6,6-spirocyclic systems (as in gymnodimine A (2) and recently isolated kabirimine (3) 3 ) being the most common. 4 Portimine A (4), isolated in 2013, is an example of a cyclic imine toxin bearing a 5,6-spirocyclic imine system.…”
Section: Introductionmentioning
confidence: 99%
“…Portimine A ( 1 ) was first isolated from the benthic marine microalga Vulcanodinium rugosum off the coast of New Zealand in 2013. It holds a special place in this family of natural products as the first natural product to be isolated that contains a five-membered cyclic spiroimine functionality. , Recently, portimine A ( 1 ) was reisolated independently by both the Strangman and Tanaka groups, along with a new derivative portimine B ( 2 ). Portimine B ( 2 ) possesses the same core scaffold as portimine A ( 1 ), except for the oxidation state at C5 and the hydrolyzed THF ring.…”
Section: Introductionmentioning
confidence: 99%